Cutaneous larva migrans - Sałamatin, Rusłan (2023)
Funding Information: We extend our sincere thanks to the patients for generously sharing their photos, as their contribution has enriched our article and knowledge, and we are truly grateful for their cooperation. This work was partially financed by grants from Wrocław Medical University (SUBZ.A060.22.054) for one of the co-authors (MW). Additionally, we express our appreciation to Laurence Taylor for diligently proofreading the article, ensuring its accuracy and clarity. Publisher Copyright: © 2023 Sałamatin et al.